Marketing de relacionamento e o papel da empatia na retenção de clientes - Trigo, Irineu Lopes (2017)
Relationship marketing has been the focus of studies and applications in several areas of business and theoretical convergence with others marketing references. However, the competitiveness, amount of offers and customer information level transformed exchange not continued insufficient for many markets. In this way, narrower relationships with customers and business partners have become drivers for the sustainable profitability of business relationships, and customer retention becoming a key concept that demands the identification of ingredients that contribute to its theoretical and practical improvement. Thus, through an exploratory research and statistical process to models that bring together non-measurable variables, this research proposed the empathy construct as relationship quality and commitment predictor and analyze its influences on customer retention. It should be emphasized that the proposed model seeks to fill a gap in relational marketing theory that has not been detected until nowadays in the academic bases. The research covered the relationship marketing literature review as well empathy, relationship quality, commitment and customer retention and the data treatment was done through the structural equation modeling by SmartPLS software. The results from analysis has shown model quality and accuracy suggesting that empathic abilities prove to be useful for managerial action in the presented context